BEAUTY THROUGH TOUCH AND SIGHT: THE SCULPTURES OF THE SRI LAKSHMI VENKATESWARA TEMPLE, KADAPA - Sri Kavya, Peddinti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the Sri Lakshmi Venkateswara temple, located in Devuni Kadapa, Kadapa district of Andhra Pradesh, India. The temple has a rich history, with influences from various dynasties that ruled the region. The focus of the paper is on the art and sculptures found on the pillars of the Ranga Mandapa. These sculptures depict a variety of subjects, including religious figures, social and cultural activities, and scenes from daily life. The paper also discusses the concept of beauty in sculptures, drawing a distinction between free beauty and adherent beauty. Free beauty can be appreciated through sight and touch, while adherent beauty is related to the purpose or function of the sculpture. The paper concludes by acknowledging the importance of the temple for the local community and its role in preserving history and culture.